2013
DOI: 10.3109/08880018.2013.806620
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Juvenile Nasopharyngeal Angiofibroma in Brazilian Patients

Abstract: Juvenile nasopharyngeal angiofibroma (JNA) is a vascular tumor of the nasopharynx that accounts for 0.5% of all cancers of the head and neck. It primarily affects males aged 14-25 years. Of the many genes that mediate the development of JNA, GSTM1 has been most frequently associated with this vascular tumor. The loss of expression of GSTM1 (null genotype) is linked to the development of these tumors. The aim of this cross-sectional case study was to examine the prevalence of the GSTM1-null genotype in Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Another study identified that GSTM1 (null genotype) is linked to the development of JNA [69]. SYK protein kinase (tyrosine kinase) is differentially expression in low and high stage JNA, suggesting a possible molecular treatment target, along with angiogenic protein basic fibroblast growth factor [70,71].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Another study identified that GSTM1 (null genotype) is linked to the development of JNA [69]. SYK protein kinase (tyrosine kinase) is differentially expression in low and high stage JNA, suggesting a possible molecular treatment target, along with angiogenic protein basic fibroblast growth factor [70,71].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…They typically present as insidious onset nasal obstruction (80–90%), epistaxis (45–60%), headache (25%), and facial swelling (10–18%) and are most often associated with a history of chronic sinusitis [ 2 – 4 ]. There are various genetic etiologies that have been proposed; however, none of these have been directly linked to nasopharyngeal angiofibromas so that a causal link is yet to be established [ 5 ]. In this case report, we present an unusual case of a nasopharyngeal angiofibroma causing obstruction acutely in an adult male.…”
Section: Introductionmentioning
confidence: 99%
“…When this is not expressed there is an increased risk of developing some malignancies [17,42]. Two studies performed on GSTM1-null genotype [17,33]. In both studies, the GSTM1-null genotype was associated with the formation of JNA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these, c-Myc [6,7,28], c-Kit (2,6,7), FLI-1 [5], endoglin [5,11], TNC [9], PCNA [10,12], Ki-67 [16], GSTM1 [17,33], AURKA and MDM2 (34) were shown to be associated with JNA. Among these, GSTM1-null genotype gene seems important.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation